HISTORY OF INDIAN PARTITION 1947 AND ITS REPRESENTATION IN FICTION AUTHORED BY BAPSI SIDHWA - Lubna Akram, ,Khadija Akram, Amna Shahid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
History and fiction have strong relation with each other. History provides themes and material to fiction so that fiction writers may create stories based on historical events. In the history of India, partition was most significant event which was followed by migration on both sides of the border. The riots, the victimization of women and large scale killing of the people followed the event of partition. This partition resulted in formation of two countries but followed much disturbance and violence. Many writers of that time write about partition and women victims as they were brutally targeted by the men of both communities. Bapsi Sidwa is amongst those writers who contribute literature by creating stories which depict the scenario of that time. The current study explains the history of partition of India 1947 as seen from the eyes of Bapsi Sidwa. Her accounts of Indian partition are important because of her feminine gender as well as she was a witness of that event and she was neither Hindu nor Muslim to may have subjectivity in her representations. Therefore, her fiction work is considered objective narrative of the Indian partition presented in this article.